1981
DOI: 10.1002/j.1537-2197.1981.tb07793.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Alpha‐amylases From the Latex of Three Selected Species of Euphorbia (Euphorbiaceae)

Abstract: A technique for the partial purification of α‐amylases from latex of Euphorbia heterophylla, E. marginata, and E. tirucalli is described. The enzymes were found to be similar to other higher plant amylases using the criteria of molecular weight, pH characteristics, kinetics, number of isozymes, and blue value‐reducing value patterns. Carbohydrases other than α‐amylases were not detectable in latex. The amylases were employed to examine their capacity to digest latex starch grains which are common components of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Bark beetles, for example, attack host trees en masse, thereby overwhelming the defensive response of their canals (Cates andAlexander 1982, Birch 1984). Besides vulnerability to behavioral deactivation, canal-borne defenses pose a second problem: when injured, they release large volumes of fluids, which are lost to the plant (although many canals have plugging agents to minimize drainage; Cronshaw et al 1973, Buttery and Boatman 1976, Biesboer and Mahlberg 1981.…”
Section: Discussionmentioning
confidence: 99%
“…Bark beetles, for example, attack host trees en masse, thereby overwhelming the defensive response of their canals (Cates andAlexander 1982, Birch 1984). Besides vulnerability to behavioral deactivation, canal-borne defenses pose a second problem: when injured, they release large volumes of fluids, which are lost to the plant (although many canals have plugging agents to minimize drainage; Cronshaw et al 1973, Buttery and Boatman 1976, Biesboer and Mahlberg 1981.…”
Section: Discussionmentioning
confidence: 99%
“…Starch accumulated in the laticifer throughout its period of growth, but apparent net starch degradation did not subsequently occur. In previous studies of laticifer starch of other Euphorbia species, no diurnal rhythm or net starch degradation in darkness was observed in contrast with that occurring in photosynthetic cells, nor was starch degraded during flowering or fruit formation (Biesboer and Mahlberg, 1978). Thus, laticifer starch does not appear to serve a storage function under any of these conditions.…”
Section: Analysis Of Latex Triterpenoids-« Triterpe-mentioning
confidence: 73%
“…The actual composition of E. esula latex starch granules was not determined; however, based on the blue-black color produced by iodine staining, it would appear that the amylose/amylopectin ratio is not unusual. Amylose content of latex starch granules from E. marginata, E. tirucalli, and E. heterophylla was determined and found to range from 18 to 20%, which is considered typical for most nonwaxy starches (2).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that they stem the flow of latex from nonarticulated laticifers when plant parts are damaged (2). What remains to be determined is why a constitutive system, which encumbers 20 to 40%…”
Section: Discussionmentioning
confidence: 99%